GLOBAL TRENDS IN BALANCED SCORECARD ADOPTION WITHIN THE EDUCATIONAL SECTOR: A BIBLIOMETRIC ANALYSIS - Ida Tejawiani; Wan Faizal, W.I.; Dani Wardani, Dian Ekawati, Lilis Sakuroh; Alias, Nor Azlina (International Journal of Teaching and Learning, 2024)
The adoption of the Balanced Scorecard (BSC) in the educational sector has grown significantly, yet global trends and implementation remain underexplored. This study aims to conduct a comprehensive bibliometric analysis to map these trends, identify influential works, and highlight regional variations in BSC research within education. The objective is to understand how educational institutions worldwide integrate BSC into their strategic management processes. Using bibliometric methods, we analyzed peer- reviewed journals from the Scopus database, focusing on BSC in education. Initially, 350 datasets were identified, refined to 192 after applying inclusion criteria, and further narrowed to 135 datasets based on relevance. The study examines publication trends, key authors, subject areas, productive countries, and influential articles. Cluster analysis identified the main research topics and emerging themes. Findings reveal significant expansion in BSC research in education over the past 26 years, with notable contributions from the United States, the United Kingdom, and Taiwan. High-impact studies focus on performance evaluation, quality management, and strategic alignment. Despite this growth, BSC research in education has not reached maturity, indicating potential for further exploration. This study fills a critical gap in bibliometric analyses of BSC in education, especially post-2018, and demonstrates the effective use of VOSviewer for mapping and visualizing data, offering insights for future research and practical applications.